Hubungan Pemanfaatan Buku Kesehatan Ibu dan Anak dengan Kepatuhan Imunisasi Dasar di Wilayah Kerja Puskesmas Ulee Kareng Kota Banda Aceh - Nazida Tur Rahmi; Khaira Rizki; Nurul Amna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Immunization is one of the most cost-effective efforts to improve maternal and child health. The proper use of Buku Kesehatan Ibu dan Anak (KIA) – Mother and Children Health Manual can server as an indicator of the quality of care provided to children in health center services. This study aims to determine the correlation between the use of KIA towards basic immunization compliance in Ulee Kareng Publich Health Center, Banda Aceh. This study employed a quantitative research design using a cross-sectional approach. The population consisted of 521 mothers with babies. The sample was 84 respondents chosen using the probability cluster sampling technique. This study was conducted in Ulee Kareng Publich Health Center from May 27 to June 24, 2025. The data were analyzed using the Chi-Square test.The results showed a correlation between the use of KIA and basic immunization compliance, with a p-value of 0.008 (P<0.05) at Ulee Kareng Public Health Center, Banda Aceh. These results indicated that mothers who used the KIA books had a better understanding of the importance of basic immunization compliance, compared to those who did not utilize them properly. It can be concluded that there is a correlation between the use of KIA books and basic immunization compliance. This study suggests that health workers provide information on the importance of the KIA books and advise mothers to use it properly.